Pengasuhan dan Perlindungan Anak dalam Undang-Undang Negara Muslim(Meninjau Resiprokalitas Keluarga dan Negara) - Maliki, Ibnu Akbar; Nurhidayati, Nurhidayati; Erwinsyah, Mardan (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
The purpose of this article is to find out the pattern of child care and protection in Muslim countries. The research method used is a documentation study of laws and regulations in Muslim countries such as Indonesia, Egypt and Tunisia. These three countries have the same pattern and orientation in child protection, which elaborates the role of the family and the state. The practical contribution of this article will provide a counter narrative to the phenomenon of violence against children that occurs in Muslim countries. The results show that child care and protection is one of the main priorities in the wheels of government in Muslim countries. The efforts made are very complex, ranging from the establishment of policies to the empowerment of formal and non-formal institutions. Partnerships and co-operation start from the family as the smallest social institution by involving all members to be actively involved in childcare, namely husband and wife. In addition, specially established government institutions also actively support the protection of children to ensure their survival and safety.